Medical treatment overview: traditional and novel psycho-pharmacological and complementary and alternative medications - Anagnostou, Evdokia (Curr Opin Pediatr, 2011)
PURPOSE OF REVIEW: Up to 35% of children and youth with autism spectrum disorder (ASD) receive at least one psychotropic medication. 50–70% of this population also receives biologically based complementary and alternative medicine (CAM). The data evaluating such practices are being reviewed. RECENT FINDINGS: There are accumulating data to suggest that atypical antipsychotics and stimulants may be useful for the treatment of irritability and hyperactivity in children and youth with ASD. The data for the use of selective serotonin reuptake inhibitors are less promising. New avenues of pharmacologic research targeting molecular targets identified by genomics, animal models and neuropathology are being evaluated. Areas of interest include glutamate/gamma-aminobutyric acid systems, neuropeptides such as oxytocin, and immune dysfunction, among others. In the case of biologically based CAM, a few compounds have been shown to be well tolerated, although efficacy is still being evaluated, such as melatonin, certain vitamins, and omega 3 fatty acids. Others have safety concerns without demonstrated efficacy, such as chelation therapies. SUMMARY: Accumulating data suggest a series of existing medications may be useful in ASD and large randomized clinical trials are necessary to evaluate safety and efficacy of both pharmaceuticals and alternative treatments.